Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Use a diagram to show that (3x+1)(x+2) is equivalent to 3x2+7x+2.

Use A Diagram To Show That 3x1x2 Is Equivalent To 3x27x2 class=

Sagot :

3x*x = 3x^2

3x*2 = 6x

x*1 = x

1*2 = 2

that's basically the FOIL method, multiply first terms, the x terms
then the outside terms, the the inside terms, then the constant (last) terms
F=first, O=outside, I = Inside, L = last

add them up to get 3x^2 +6x +x + 2 = 3x^2 +7x +2

(3x+1)(x+2) = 3x^2 +7x+2

draw a rectangle with one side as 3x+1, the other side as x+2. The area of the rectangle is their product

divide the rectangle into 4 smaller rectangles. with sides 3x by x, 3x by 2, x by 1 and 2 by 1
calculate the areas of each rectangle the sum them.

standard form is

y=ax^2 +bx + c or

f(x) = x^2 +7x +2 where a=1, b=7, c=2

another standard form is to put the quadratic equation in vertex form
by completing the square

f(x) or y = x^2 +7x + 49/4 = -2 + 49/4

y = (x+3/2)^2 = 41/4

where the vertex = (3/2,41/4)

standard equation in vertex form is

y= a(x-h)^2 + k where (h,k) = vertex = (3/2,41/4) with a=1

It's an upward opening parabola with y intercept = 41/4 = 10 1/4, axis of symmetry x=3/2
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.